Affirmative action at work: a survey of graduates of the University of California, San Diego, Medical School. - Penn, N E (1986)
Reported here are the results of a mail survey of 113 graduates from the University of California, San Diego, School of Medicine. Fifty-seven had been admitted with assistance of the Special Admissions Subcommittee (SAS) and 56 had been admitted through the traditional Recruitment and Admissions Committee mechanisms. SAS graduates see more patients daily, and practice more often in primary care specialties in rural and inner-city areas, providing medical care for ethnic minorities from lower socioeconomic strata.